Editorial introduction - Jermaine S. McDougald (Universidad de La Sabana, 2015)
Welcome to Volume 8, Issue 1 of the Latin American Journal of Content and Language Integrated Learning (LACLIL). This issue presents a variety of research endeavors on how content and language are being treated at different levels of education. Nowadays, the progression of foreign language teaching and each of its methods and approaches are taking place in a framework in which the term innovation is fundamental. The pace of globalization has been rapidly increasing, strongly affecting cooperation and communication across cultures. This is why it is very important that practitioners and researchers alike participate in making the teaching and learning process much more meaningful in the twenty-first century classroom. Therefore appreciating and analyzing our own cultural perspective against foreign cultural perspective are essential elements in the development of intercultural competence